2006
DOI: 10.1785/0120060015
|View full text |Cite
|
Sign up to set email alerts
|

Buildings as a Seismic Source: Analysis of a Release Test at Bagnoli, Italy

Abstract: Taking advantage of a large displacement-release experiment on a twostory reinforced concrete building located in Bagnoli (Naples, Italy), we performed free-field measurements using 3D seismometers, accelerometers, and a 100-m-long vertical array. The ground motion was noticeable: near the building, the acceleration exceeded 5% g. At each measurement point, it was possible to recognize two source terms, due to the tested building and to the reaction structure. The two sources generated different wave trains. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…If the reference site is located outside the building on the foundation soil, but very close to the building, its vibrations could influence the recordings. This effect increases if the building frequency is in the same range of the soil frequency [11,12,32,33].…”
Section: Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…If the reference site is located outside the building on the foundation soil, but very close to the building, its vibrations could influence the recordings. This effect increases if the building frequency is in the same range of the soil frequency [11,12,32,33].…”
Section: Methodologiesmentioning
confidence: 99%
“…[11,12]), but again these detailed approaches can be used only for a limited number of selected buildings. Hans et al [13] demonstrated that impacts, forced vibration and ambient noise yield the same values for fundamental periods of building in Lyon, France.…”
Section: Introductionmentioning
confidence: 99%
“…The radiated energy is visible also in the vertical component because the building-radiated wave field is a mix of body and Rayleigh waves (Guèguen et al, 2000, Mucciarelli et al, 2003Gallipoli et al, 2006).…”
Section: Building-soil Interactionmentioning
confidence: 99%
“…et al, 2004;Cornou C. et al, 2004), or snap-back test on both models (Guéguen. et al, 2002) and real buildings (Mucciarelli et al, 2003;Gallipoli et al, 2006;Ditommaso et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the spectral ratios between the ambient vibrations Fourier spectra of horizontal components (HHSR), which are evaluated at the base and the different building levels, were used to determine the dynamical properties of this structure. These kinds of studies are important in investigating the possible soil-structure resonance effects that can arise when the fundamental frequency of a building shares the same range as that observed in the foundation soil [33][34][35]. …”
Section: Introductionmentioning
confidence: 99%